Comparative Analysis of Methyl Red Adsorption on NaOH- and HCl-Activated Carbon from Bintaro Fruit: Kinetics and Isotherm Studies (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2024)
Pollution caused by synthetic dye waste poses a significant environmental challenge, especially in the textile industry. This study aims to develop activated carbon from bintaro fruit (Cerbera manghas) activated with HCl and NaOH, to function as a bio adsorbent in eliminating methyl red from water-based solutions. Characterization of the activated carbon revealed that NaOH activation resulted in a larger surface area and porosity compared to HCl activation. Adsorption kinetics tests revealed that the adsorption mechanism was better represented by the pseudo-second order model, with higher R² values for both adsorbents (0.951 for HCl and 0.985 for NaOH). Adsorption isotherm results demonstrated that Langmuir model provided a better fit for describing methyl red adsorption, with highest adsorption capacities were 13.18 mg/g for NaOH-activated carbon and 8.65 mg/g for HCl-activated carbon. Thus, NaOH-activated bintaro fruit carbon exhibited higher adsorption efficiency than HCl-activated carbon, making it a potential alternative for environmentally friendly dye waste treatment